Challenges from new trends in foreign direct investment - Wilfried Lütkenhorst (Intereconomics, 1988)
Foreign direct investment flows to developing countries have undergone major changes in recent years, both regarding their scope and their determinants. This article reviews some new trends in this area and focuses specifically on their implications for export processing zones which in the past have been a widely used instrument to attract foreign investment. How are they affected by the new developments and what can be their role in the future?
Keywords: 330; Export Processing Zones